2022
DOI: 10.21037/tau-21-900
|View full text |Cite
|
Sign up to set email alerts
|

Testis-enriched Asb12 is not required for spermatogenesis and fertility in mice

Abstract: Background: Members of the ankyrin repeat and SOCS box (Asb) family are expressed abundantly in testes. Some Asb genes/proteins are required for spermatogenesis, but the function of Asb12 during spermatogenesis is not clear. We investigated the physiological role of Asb12 in murine testes. Methods:The clustered regularly interspaced short palindromic repeats/CRISPR-associated protein 9 system was used to generate Asb12-knockout (KO) mice. Histology and immunostaining were done to assess the effects of Asb12 KO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…The reproductive parameter results indicated that Fbxo22 is not required for spermatogenesis or male fertility. Currently, research findings suggest that numerous genes encoding ubiquitin enzymes expressed in the testis are not necessary for mouse fertility (e.g., ankyrin repeat and SOCS box containing 12 (Asb12) [25], Asb15 [26], F-box and WD-40 domain protein 17 (Fbxw17) [27]). Our findings eliminate Fbxo22 as a target for contraception and as a factor in male infertility, which can prevent redundant research efforts and save resources in other laboratories.…”
Section: Discussionmentioning
confidence: 99%
“…The reproductive parameter results indicated that Fbxo22 is not required for spermatogenesis or male fertility. Currently, research findings suggest that numerous genes encoding ubiquitin enzymes expressed in the testis are not necessary for mouse fertility (e.g., ankyrin repeat and SOCS box containing 12 (Asb12) [25], Asb15 [26], F-box and WD-40 domain protein 17 (Fbxw17) [27]). Our findings eliminate Fbxo22 as a target for contraception and as a factor in male infertility, which can prevent redundant research efforts and save resources in other laboratories.…”
Section: Discussionmentioning
confidence: 99%
“…Fertility is an important function, and there may be redundant genes with overlapping functions to ensure stability of individual fertility. Asb-1, 2, 3, 4, 5, 7, 8, 9, 11, 14, 15 , 17 , and 18 genes are expressed at significantly higher levels in Asb12 -KO mice than in Asb12 -WT mice ( Zhang et al, 2022 ). The Slc26a family is highly conserved, with 11 members in mice (SLC26A10 is a pseudogene in humans).…”
Section: Discussionmentioning
confidence: 99%
“…At present, study findings indicate that many genes expressed in the testis are dispensable for mouse fertility ( e.g ., FBXW17 ( Chen et al, 2022b ), ASB12 ( Zhang et al, 2022 ), USP26 ( Felipe-Medina et al, 2019 )). Our results exclude SLC26A1 as a contraceptive target and male infertility factor and will help avoid duplication of effort by researchers and save time and money in other laboratories.…”
Section: Discussionmentioning
confidence: 99%